APPAREL PURCHASE DECISIONS: THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, AND DESIGN - Nurdin, Hairil; Masri, Syahril; M. Jusuf, Ardi (Journal of Entrepreneur, Business and Management, 2023)
This research aims to determine the influence of product quality, promotion and design on purchasing decisions for Manzone distro clothing. This research uses quantitative methods with a survey approach. The sample in this study was 100 respondents. Sampling used the Slovin technique with a non-probability sampling technique. The results of this research show that product quality has a positive and significant influence on purchasing decisions, promotion has a positive and significant influence on purchasing decisions, design has a positive influence on purchasing decisions, and simultaneously product quality, promotion and design have a significant influence on purchasing decisions for Manzone distro clothing. Keywords: Product Quality, Promotion, Design, Purchasing Decisions